The Sabhara Unit Patrol Efforts in Preventing the Crime of Theft With Violence in the Legal Territory of the Makassar Police - Rahmat Putra Ramadhan (Advances in Police Science Research Journal, 2021)
This research is motivated by the high number of criminal acts of theft with violence (curas) in Makassar City. As the backbone of the police force and as a crime prevention measure, the Sabhara unit patrol plays a major role in this problem. This study aims to analyze the role of the Sabhara unit patrol in preventing the crime of violent theft, the factors that influence the implementation of the Sabhara unit patrol and how to increase the effectiveness of the Sabhara unit patrol at the Makassar Police Station. This research was conducted using a qualitative approach and data collection techniques by interview, observation, and document study. From this research, it can be seen that there is a real picture of the prevention efforts carried out by the Makassar Police Sabhara unit against the crime of stealing. To process the data obtained by researchers using the theory of employee performance, Perkabaharkam Number 1 of 2017 concerning Patrols and the Promoter concept launched by the National Police Chief. The results of the study found that the role of the Sabhara patrol unit had not been fulfilled optimally because the performance of employees had problems in the aspects of input, process, output and results. This is influenced by several inhibiting factors, namely individual factors such as the ability of untrained patrol officers, system factors in the form of negative work culture of the Sabhara unit and contextual factors in the form of society and an unsupportive work environment. Based on the results of the study, the authors suggest eliminating a negative work culture in the Sabhara unit, implementing a patrol strategy that is in accordance with Perkabaharkam Number 1 of 2017 concerning Patrols, as well as equal distribution of personnel placement and special training for patrol skills. Thus the role of the Sabhara Polres Karanganyar patrol unit in preventing the crime of stealing can be fulfilled optimally.